Will DANCAVAS be the most important screening trial in the last 50 years? - Neal M. Dixit; Edward Chau; Saul Schaefer (Elsevier, 2024)
Screening trials for cardiovascular disease have not demonstrated a reduction in all-cause mortality. The Danish Cardiovascular Screening trial (DANCAVAS) involved men aged 65-74 years old who were randomized to an invitation to undergo screening or not. While the 5-year interim analysis did not show a statistically significant benefit in the primary outcome of all-cause mortality, HR 0.95 (CI 0.90-1.00), a sub-group analysis of men age 65-69 did show a lower hazard ratio of 0.89 (CI 0.83-0.96). Given the widening difference between screened and un-screened participants, as well as the benefit in younger subjects, it is likely that the next analysis will demonstrate a statistically-significant benefit of screening. In this commentary we argue why this trial will almost certainly become one of the most influential screening trials and why heeding its most important lesson, the use of coronary artery calcium scoring, has the potential to save countless lives.